Efecto de dosis de lactasa y sacarosa como edulcorante en la obtención de una bebida isotónica a partir del lactosuero dulce - Intriago Cobeña, Rubén Darío (2017)
This investigation was created with the objective of evaluating the effects of the addition of lactase (B-Galactosidase) and saccharose (like sweetener) to obtain an isotonic drink from a sweet lactuser. Two factors were established in study: Factor "A" dose of lactase 5200 NLU in doses of 0.5ml, 1.1ml, and 3ml and as Factor "B" percentages of sucrose in 7 and 8, the experimental unit was 18.18kg of a sweet whey, distributed in six treatments with three replicates each; formulating combinations: TI (0.5:7), T2 (0.5:8), T3 (1.1:7), T4 (1.1:8), T5 (3:7), T6 (3:8). The variables that were evaluated are: energy and carbohydrates. The results of the ANOVA showed significant differences for the carbohydrate variable on the treatments, and showed significant differences for Factor "B" on the variable carbohydrates. T2 was determined as the best treatment on the bases of an affective test. The analysis of sodium and potassium electrolytes performed on the same T2 showed that sodium was the only one that complied with the values established by the NTC 3837. The addition of various doses of lactase did not affect the substantial parameters of an isotonic drink. The percentages of sucrose considered in the formulation to obtain the beverage had a significant effect on the response variables. Providing a higher carbohydrates and energy value than indicated by the standard and by some experts, respectively